Thyroid function in individuals living with human immunodeficiency virus: the concern and debate about regular screening - Ibrahim, Maryam; Adeniran, Anjola; Ibrahim, Mariam A.; Woodward, Clare; Mital, Dushyant; Ahmed, Mohamed H. (Annals of Thyroid; Vol 4 (July 2019): Annals of Thyroid, 2019)
Abnormal thyroid functions are common among individuals living with human immunodeficiency virus (HIV). Potent antiretroviral therapy can induce abnormalities in thyroid function or it can be related to drug interactions and the immune reconstitution inflammatory syndrome (IRIS). Increasing prevalence of thyroid dysfunction has been reported in individuals living with HIV (LWHIV). However, there is insufficient evidence to recommend routine thyroid screening of asymptomatic individuals. Hence, in this review we report the common thyroid dysfunctions associated with HIV and in association of anti-retroviral therapy (ART); after critical review of PubMed and Google scholar published-English literature since 1996. HIV can be associated with hypothyroidism, hyperthyroidism and also may increase the risk of thyroid cancer. Emerging evidence also showed that in well treated individuals LWHIV, thyroid function may not be affected by HIV. Therefore, it is a good clinical practice to screen for thyroid function once every 12–24 months. Currently there is little research about the impact of aging in thyroid function in individuals living with HIV. Further research is also needed to establish the value and interval of regular screening of thyroid function in individuals living with HIV.